Kin with no skin: Johanson-Blizzard syndrome in siblings: A rare association of aplasia cutis congenita - G S Asha; K Kavya Shree; T N Revathi; Kanathur Shilpa (Wolters Kluwer Medknow Publications, 2021)
Johanson-Blizzard syndrome (JBS) is a rare autosomal recessive disease which was first described in 1971 by Johanson and Blizzard in three unrelated girls. Less than 100 cases have been reported to date. It is characterized by exocrine pancreatic insufficiency, hypoplastic nasal alae, scalp cutis aplasia, and other features including developmental delay, failure to thrive, hearing loss, mental retardation, hypothyroidism, dental anomalies, and anomalies of the genitourinary system. The condition is caused by mutations in the UBR1 gene, which encodes the E3 ubiquitin ligase protein responsible for regulating the degradation of proteins. Aplasia cutis congenita is a rare entity characterized by localized or widespread absence of skin from birth. Scalp is the most common site to be involved. Here, we are reporting two interesting cases of JBS in siblings who had aplasia cutis as their initial cutaneous manifestation.